«Pel vantaggio della Republica letteraria». The Bibliographical Correspondence between Girolamo Tiraboschi and Carlo Carlini - Lucrezia Signorello (TECA)
The essay focuses on the correspondence exchanged, from 1781 to 1788, between Girolamo Tiraboschi, librarian of the Duke of Modena, and Carlo Carlini, the first custodian of the Royal Library of Brera. The 51 preserved missives constitute a piece, still virtually unpublished, of the dense information network that connected the farthest outposts of the Respublica litteraria to Tiraboschi’s desk. What emerges from the correspondence is a relationship that was far from being purely and strictly work-related, having quickly become friendly: in the letters, indeed, one finds both erudite information, book exchange agreements, requests for bibliographic checks, and numerous notes relating to the more private sphere. The epistolary thus provides a vivid insight into the professional and intellectual activities of the two correspondents, as well as a more three-dimensional reconstruction of their personalities.